TOTAL QUALITY MANAGEMENT IN HOSPITALITY INDUSTRY: MEASURE OF SERVICE QUALITY - Vaidyanathan, Sakthi Praveen (2015)
The report is created as a result of rigorous thesis, anti-thesis and synthesis. The presented thesis/dissertation is based on the concept of TQM, also known as Total Quality Management in hospitality industry. In doing so, the industry has been scrutinized to a magnified level where all its elements are featured from bi-dimensional perspective i.e. of the customers‘ as well as of the management‘s. This discusses topics that have the ability or capacity to define the term in an analytical way. SERVQUAL is one of the major applications that have been discussed here, with an intricate assessment on the same. This entails the utilization of the same in the field of hospitality. Moreover, one must know the fact the concept of hospitality is service oriented and aimed at meeting the needs of the customers; therefore, the management of any random company should be in a position to evaluate the impacts of its tangible and intangible provisions and hence, improvise on the same if needed. In order to incorporate management limitation the SERVQUAL model was modified, this modified model has been tested in few hotels and restaurants. Hereby, a detailed approach has been taken in this thesis presentation. Apart from all these, a correlation has been attempted to be established through studying the questionnaires designed as per both the perspectives.